Human endogenous retrovirus transcription profiles of the kidney and kidney-derived cell lines - Haupt, Sonja; Tisdale, Michele; Vincendeau, Michelle; Clements, Mary Anne; Gauthier, David T.; Lance, Raymond; Semmes, O. John; Turqueti-Neves, Adriana; Noessner, Elfriede; Leib-Mösch, Christine; Greenwood, Alex D. (Journal of general virology, 2011)
The human genome comprises approximately 8-9% of human endogenous retroviruses (HERVs) that are transcribed with tissue specificity. However, relatively few organs have been examined in detail for individual differences in HERV transcription pattern, nor have tissue-to-cell culture comparisons been frequently performed. Using an HERV-specific DNA microarray, a core HERV transcription profile was established for the human kidney comparing 10 tissue samples. This core represents HERV groups expressed uniformly or nearly so in non-tumour kidney tissue. The profiles obtained from non-tumour tissues were compared to 10 renal tumour tissues (renal cell carcinoma, RCC) derived from the same individuals and additionally, to 22 RCC cell lines. No RCC cell line or tumour-specific differences were observed, suggesting that HERV transcription is not altered in RCC. However, when comparing tissue transcription to cell line transcription, there were consistent differences. The differences were irrespective of cancer state and included cell lines derived from non-tumour kidney tissue, suggesting that a specific alteration of HERV transcription occurs when establishing cell lines. In contrast to previous publications, all known HERV-derived tumour antigens, including those identified in RCC, were expressed both in multiple RCC cell lines and several non-tumour tissue-derived cell lines, a result that contrasts with findings from patient samples. The results establish the core kidney transcription pattern of HERVs and reveal differences between cell culture lines and tissue samples.,
Gesehen am 07.09.2022